Hidden IgG4-Related Coronary Disease: An Autopsy Study. Issue 3 (19th March 2021) - Ramdin, Namita; Orde, Matthew; O'Neill, Siobhán B; Lai, Chi; Pors, Jennifer D; Multan, Michael; Chen, Luke Y C; Carruthers, Mollie N
Abstract: Objectives: We present a full autopsy with a focused radiology and pathologic review of the coronary arteries. We hope that the results described in this article will help create better diagnostic measures and prevent future coronary artery vasculitis misdiagnosis. Methods: A full autopsy was performed on the body of Dr Myung Choong Yoon, with full consent from the family, within the department of pathology and laboratory medicine at Vancouver General Hospital. Tissue samples from the heart, brain, lungs, and spinal cord were submitted to specialist pathologists for histologic processing. Results: Cardiac gated computed tomography coronary angiography suggested periarteritis. Coexistent calcified coronary atherosclerosis with linear calcifications was present along the luminal wall, along with coronary artery ectasia. Histologic assessment confirmed features of dense adventitial fibrosis around the coronary arteries, with an exuberant lymphoplasmacytic infiltrate and numerous plasma cells consistent with IgG4-related disease. The media of the coronary arteries was markedly attenuated or completely absent, which likely contributed to the coronary arterial ectasia noted microscopically. These findings confirmed IgG4-related coronary arteritis. Conclusions: Coronary periarteritis is an uncommon manifestation of IgG4-related disease established radiographically and later by autopsy.